Integrating Geometry in Teaching Square of A Binomial â€“ A Lesson Study - Gerald Cerezo, Mark; Cristobal, Karlo; Ferrer, Angelo; Mae Moreno, Helen; Ocampo, Nico; Elipane, Levi (International Journal of Engineering and Technology, 2018)
This paper intends to discuss the benefits of doing lesson studies in order to improve teaching practice in Mathematics. Fifteen Grade 8 students from a private school in the National Capital Region, Philippines participated in the study. The group followed the cycle of planning the lesson, implementing, and discussing what transpired from teaching the research lesson. The lesson study is about integrating geometry in obtaining the square of a binomial. After planning the lesson and implementing what has been discussed, it has been agreed upon that the objective of the lesson has been met, and that is to relate areas in squaring a binomial. Afterwards, a post-conference discussion was done. It has been emphasized that in order to teach Mathematics effectively and efficiently, a teacher must consider and be aware of the appropriateness of a lesson given a limited amount of time. Additionally, highlighting wrong answers must be done so that students will be able to process what caused those errors and in turn they will be able to avoid those mistakes. Lastly, it is also evident that a teacher should craft his or her skills in the art of questioning. Thus, conducting lesson studies improve teaching practices in mathematics.Â Â